The role of feedback in athlete learning - Paliaga, M. (EWF Scientific Magazine, 2017)
One of the most important aspects related to the problems of motor control, and therefore also learning, is related to the phenomena that affect feedback. Feedback is all the information that the individual who carries out a movement has the ability to receive and process, and that allows him to control the movement and perform it more effectively. It is critical that the coach stimulates interest and attention in young athletes, to solicit the conscious and responsible participation in the physical activity, especially when it is directed to learning and mastering techniques. Young athletes must be enthusiastic and involved in their own learning process in order to reach the necessary autonomy to manage it themselves.